Exploring Innovative Pedagogy in the Teaching and Learning of Chinese as a Foreign Language - Moloney, Robyn; Xu, Hui Ling (Multilingual Education, 2016)
Teachers of Chinese as a foreign language in many international contexts are searching for pedagogic solutions to promote effective learning. Models of innovative and successful approaches are urgently needed. This volume presents a collection of compelling and empirically rich research studies that showcases innovative developments in the practice of teaching Chinese as a foreign language. The studies focus on three interrelated areas: learners, teachers, and applications of new technologies. Specifically, the studies explore methods for fostering learner-centred classrooms, autonomous learners, intercultural learning, the role of teacher views and identities, the nature of a 'middle ground' approach, and technologies that accommodate the unique aspects of the Chinese language, with new options for mobile and interactive learners. Providing both inspiration and practical models for language practitioners and researchers, it offers a vital resource for teachers' professional development, and for pre-service teacher education.